Role of person ’ s ideological orientations in the world view formation and the self-image - Volodarskaya, Natalia (Social Welfare: Interdisciplinary Approach, 2014)
The article describes features of the influence of ideological orientations of personality on building a picture of the world and the self-image. It defines specificity of self-cognition, self-realization and self-identity process in adolescence. Determinants of ideological orientations formation are mentioned. The features of synergistic approach to the study of world view formation, the self-image, the hierarchy of personal values in a contemporary environment are considered. Differences were defined of life values, senses, perceptions about the meaning of life between creative and talented high school students and other high school students from regular schools. The influence of social and cultural factors on these differences (social status of parents of high school students, the prestige of school) is analyzed.